Collagen biogenesis and assembly into fibrils as shown by ultrastructural and 3H‐proline radioautographic studies on the fibroblasts of the rat foot pad - Marchi, Fausto [UNESP]; Leblond, C. P. (Wiley, 1983)
To examine whether collagen is assembled into fibrils within or outside fibroblasts, the connective tissue of the rat foot pad was investigated by electron microscopy and by radioautography at times varying from 4 min to 3 days after an intravenous injection of 3H‐proline. The fibroblasts of the rat food pad are long polarized cells with the nucleus at one end, the Golgi apparatus in the center, and a region with long processes at the other end. This region contains secretory granules and is considered to be the secretory pole of the cell. In the Golgi apparatus the stacks of saccules are separated from rough endoplasmic reticulum (rER) by groups of “intermediate vesicles” including similarly structured tubules which may be over 300 nm long and are referred to as “intermediate tubules”. The Golgi saccules exhibit distended portions which differ at the various levels of the stack. On the cis side, the distentions tend to be spherical and contain fine looping threads; in the middle of the stack, they are cylindrical and present distinct straight threads; whereas on the trans side, they are again cylindrical, but the straight threads are grouped in parallel aggregates. Between these cylindrical distentions and the secretory granules, there are transitional forms within which thread aggregates are packaged more and more tightly. Finally, the fibroblasts are associated with two types of collagen fibrils: extracellular ones arranged into large groups between the cells and intracellular ones located within long intracytoplasmic channels. Quantitative radioautography after 3H‐proline injection reveals that the number of silver grains per unit area reaches a peak over the rER at 4–10 min, Golgi apparatus at 40 min, secretory granules at 60 min, and extracellular collagen fibrils at 3 h. At no time are intracellular collagen fibrils labeled. Qualitative observations further indicate that spherical Golgi distentions are mainly labeled at 40 min, and cylindrical distentions, at 60 min. In addition, from 20 min to 3 hr, some lysosomal elements are labeled. The biogenetic pathway leading to the formation of collagen fibrils is interpreted as follows. Collagen precursors arise in the rER and, by way of intermediate tubules or vesicles, reach the spherical Golgi distentions. These seem to migrate in a trans direction, while they become cylindrical and their looping threads straighten out into rods which have been identified as procollagen. The cylindrical distention is then freed from its saccule to become a secretory granule. The procollagen content of the granule is released outside the cell and presumably transforms into collagen which then polymerizes into fibrils. Thus, except for a minor fraction of the labeled precursors deviated toward the lysosomal pathway, the bulk of them give rise to collagen, which is added to the extracellular fibrils and, therefore, provides for their growth. No collagen is incorporated into the intracellular collagen fibrils, which, therefore, do not grow, but often undergo degeneration. Thus, the assembly of collagen into fibrils does not occur within cells but is entirely extracellular. Copyright © 1983 Wiley‐Liss, Inc.